Exploring micro- and macro-levels of discourse in digital parent-teacher communication: a methodological framework - Gamliel, Reut Chen; Kupferberg, Irit (Frontiers in Education, 2025)
Current studies have foregrounded the contribution of discourse analysis to the study of the internet as a preferred interaction medium where social, psychological, cultural, and professional dimensions of meaning are co-constructed in naturally occurring communication. Studies have also emphasized the significance of parental partnerships with others regarding the wellbeing and success of pupils. However, little research has systematically examined how parents and teachers engage in digital communication during times of crisis and how meaning is negotiated within these interactions. The present study aims to address this gap by presenting and illustrating a discourse-oriented methodological framework designed to analyze meaning construction in a digital parent-teacher forum. This framework integrates both micro and macro analytic levels to explore discourse dynamics in digital interactions. Guided by Conversation Analysis, Discursive Psychology, and Positioning-Displaying Language Analysis, which favor naturalistic interaction as the object of analysis, the microanalysis explores (1) the specific discursive actions performed by forum participants in interactional post sequences and (2) the ways in which these participants position themselves in digital written discourse. The macro-analytic lens is guided by Positive Discourse Analysis, a critical approach emphasizing that “critical” does not necessarily imply “being negative” but rather includes the proposition of alternatives and the facilitation of constructive change within educational discourse. The analysis revealed that initial posts shaped the trajectory of interaction, with participants discursively positioning themselves through figurative language and textual strategies. Teachers often portrayed themselves as fighters, while some parents responded with critical metaphors, highlighting tensions and identity negotiations. A turning point emerged when a participant redirected the discussion toward systemic reform, offering a constructive discursive path. These findings underscore the value of interpretative pluralism in understanding stakeholder interactions and suggest that digital forums can foster inclusive dialogue, though they may be limited in driving institutional change.